2021
DOI: 10.3390/genes12010067
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Approach Reveals miR-SNPs Affecting Muscle Fatty Acids Profile in Nelore Cattle

Abstract: MicroRNAs (miRNAs) are key regulators of gene expression, potentially affecting several biological processes, whose function can be altered by sequence variation. Hence, the integration of single nucleotide polymorphisms (SNP) and miRNAs can explain individual differences in economic traits. To provide new insights into the effects of SNPs on miRNAs and their related target genes, we carried out a multi-omic analysis to identify SNPs in miRNA mature sequences (miR-SNPs) associated with fatty acid (FA) composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…In summary, a potential effect of the rs319154814 (G/A) SNP in the synthesis or degradation of myristic acid can be envisaged, but this hypothesis still needs to be confirmed at the functional level. Interestingly, Cardoso et al (2021) [99] explored the relationship between miRNA SNPs located in the seed and mature regions of bovine miRNA loci and fatty acid composition traits. By combining lipid-related phenotype data with mRNA and protein abundances in a multi-omics approach, they described three miRNA SNPs significantly associated with several unsaturated and polyunsaturated fatty acid traits, as well as with the expression levels of some of their predicted targets [99].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, a potential effect of the rs319154814 (G/A) SNP in the synthesis or degradation of myristic acid can be envisaged, but this hypothesis still needs to be confirmed at the functional level. Interestingly, Cardoso et al (2021) [99] explored the relationship between miRNA SNPs located in the seed and mature regions of bovine miRNA loci and fatty acid composition traits. By combining lipid-related phenotype data with mRNA and protein abundances in a multi-omics approach, they described three miRNA SNPs significantly associated with several unsaturated and polyunsaturated fatty acid traits, as well as with the expression levels of some of their predicted targets [99].…”
Section: Discussionmentioning
confidence: 99%
“…An Irish study has revealed polymorphisms in bovine miR-2419 modify its binding properties to target genes related to milk production (Braud, 2017). A recent multi-omics analysis shows that miR- 2419-3p is associated with muscle fatty acid traits of Nelore cattle, which may exhibit regulatory function at mRNA or protein level (Cardoso et al, 2021). In a previous study, miR-7861 was differentially expressed as a unique miRNA in Bovine serum compared to EX (Zhao et al, 2016).…”
Section: Plasma Ev and Ex Exhibit Unique Differentially Expressed Mirna Profilesmentioning
confidence: 95%
“…genome/transcriptome/proteome/ metabolome) to be integrated together in a multi-omics approach (Da Silva Diniz & Ward, 2021). Recent studies have taken such an approach to refining genomic regions and lists of potential candidate genes in pork (Welzenbach et al, 2016) and beef (Cardoso et al, 2021) and it is likely to grow in importance in future livestock studies. While SNP variation can be profiled with SNP chips and modern sequencing methods, other types of variation such as copy number variation and variation in low complexity repetitive regions are more challenging to routinely score in populations, and they potentially account for a substantial proportion of the so-called "missing heritability" observed in many livestock genomic traits, that is, heritability not accounted for by common SNP variants.…”
Section: Future Trends Of Genomics and Transcriptomics In The Field O...mentioning
confidence: 99%